2013
DOI: 10.1007/s00192-013-2233-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for urinary incontinence 1 year after the first vaginal delivery in a cohort of primiparous Danish women

Abstract: SUI or MUI 1 year after the first vaginal delivery was strongly associated with UI during the pregnancy and inversely associated with oxytocin augmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
1
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 22 publications
4
35
1
6
Order By: Relevance
“…It is also known that certain symptoms such as frequency, nocturia and urge incontinence (common in pregnancy) decrease significantly and tend to disappear in the postpartum period (25) . Parity has been reported as a risk factor for UI (25)(26)(27) , which was also demonstrated in this study.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…It is also known that certain symptoms such as frequency, nocturia and urge incontinence (common in pregnancy) decrease significantly and tend to disappear in the postpartum period (25) . Parity has been reported as a risk factor for UI (25)(26)(27) , which was also demonstrated in this study.…”
Section: Discussionsupporting
confidence: 86%
“…A relationship between UI in pregnancy and weight gain of pregnant women has been reported as a risk factor for pelvic floor muscle dysfunction (25) . A postpartum strategy for UI prevention is pelvic floor muscle training and postpartum weight loss (26) . It is also known that certain symptoms such as frequency, nocturia and urge incontinence (common in pregnancy) decrease significantly and tend to disappear in the postpartum period (25) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although gravidic changes may contribute to UI after childbirth 21 , some authors present evidence that, when present in pregnancy, this condition becomes a risk factor for its occurrence also in postpartum 7 , 21 - 22 . …”
Section: Discussionmentioning
confidence: 99%
“…Associations between birth weight greater than 8 pounds and postpartum urinary incontinence were found in 2 studies: Boyles et al described a small increased risk (OR, 1.29; 95% CI, 1.10‐1.52), as did the research by Glazener and colleagues (OR, 1.56; 95% CI, 1.12‐2.19) . Oxytocin augmentation appears to be protective (OR, 0.5; 95% CI, 0.3‐0.9) . Two studies found no association between epidural analgesia and postpartum SUI .…”
Section: Risk Factors For Urinary Incontinencementioning
confidence: 99%